P340 Vedolizumab in the treatment of chronic refractory pouchitis: a systematic review. (25th January 2019) - Lim, W-C; Lin, H
Abstract: Background: Approximately 50% of patients with ileal pouch anal anastomosis (IPAA) develop pouchitis, with 10–15% of acute pouchitis developing chronic pouchitis (CP). Whilst the majority responds to antibiotic therapy, treatment options for chronic antibiotic-refractory pouchitis (CARP) include combination antibiotic therapy, budesonide, immunomodulators (IM) or anti-tumour necrosis factor (TNF) antibodies. There is limited data on the role of vedolizumab (VZB), an a4b7 integrin antagonist, in the treatment of CP. We performed a systematic review of the literature to explore the efficacy of VZB in CP. Methods: A systematic literature search in MEDLINE (1966–November 2018), Cochrane Central Register of Clinical Trials, and abstracts from recent major gastroenterology meetings (Digestive Disease Week, United European Gastroenterology Week and Congress of European Crohn's and Colitis Organisation) was performed using the following terms: 'integrin', 'vedolizumab', 'pouchitis'. Only English language publications and abstracts on the efficacy of VZB for CP in ulcerative colitis patients with IPAA were included; Crohn's disease of the pouch was excluded. Additional trials were identified through review of reference list of included articles Results: Six case reports ( n = 6) 1–6 and 3 retrospective case series 8–10 (2 in abstract form, n = 51) were included; 1 case series (Philpott J 2017) 7 was excluded (duplicate). Only 1 ongoing randomised-controlled phase IV study (NCT02790138) was found whose data has yet to be reported. All patients ( n = 57) had chronic antibiotic-refractory/dependent pouchitis and received VZB after failing prior therapy, including IM and anti-TNF. In the case reports, 1–6 six patients (mean age 36 years, M:F 1:1) with CARP received induction/maintenance VZB; symptom improvement was seen as early as 6 weeks and pouchoscopy at 14–33 weeks reported near/complete resolution of pouchitis. In the 3 retrospective case series, 64–75% achieved improvement/clinical remission (CR) at 12–14 weeks, with 58.3% still in CR at 46 weeks: (a) 14 of 19 (73.7%) with CARP who received at least 1 dose of VZB had improvement of modified Pouchitis Disease Activity Index (mPDAI) at 12 weeks (median decrease 2 units, p = 0.031) 9 ; (b) 9 of 12 (75%) who received induction/maintenance VZB achieved CR (mPDAI< 5 + decrease of ≥2) at 14 weeks, with 7 (58.3%) still in CR at median 46(14–105) weeks 10 ; (c) after 3–4 doses of VZB, 64% with CARP/antibiotic-dependent pouchitis achieved CR (PDAI<7) 8 at 14 weeks. Minor adverse events were reported in 10–16%. 8–10 Conclusions: From uncontrolled studies and case reports, VZB appears to be efficacious and safe for the treatment of CP refractory to antibiotics and other therapy including anti-TNF. Controlled data are needed to confirm its efficacy in this group of patients. References 1. Martins D, Ministro P, Silva A, Refractory chronic pouchitis and autoimmune hemolytic anemia successfully treated with vedolizumab. Port J Gastroenterol 2018;25:340–1. 2. Orfanoudaki E, Foteinogiannopoulou K, Koutroubakis LE, . Use of vedolizimab in a patient with chronic and refractory pouchitis. Ann Gastroenterol 2018;31:379. 3. Coletta M, Paroni M, Caprioli F. Successful treatment with vedolizumab in a patient with chronic refractory pouchitis and primary sclerosing cholangitis, J Crohns Colitis, 1507–1508, 11 4. Mir F, Yousef MH, Partyka EK, et al. Successful treatment of chronic refractory pouchitis with vedolizumab. Int J Colorectal Dis 2017;32:1517–18. 5. Bethege J, Meffert S, Ellrichmann M, et al . Combination therapy with vedolizumab and etanercept in a patient with pouchitis and spondylarthritis. BMJ Open Gastroenterol 2017;4:e000127. 6. Schmid M, Frick JS, Malek N, et al. Successful treatment of pouchitis with vedolizumab, but no fecal microbiota transfer (FMT), after proctocolectomy in ulcerative colitis. Int J Colorectal Dis 2017;32:597–8. 7. Philpott J, Ashburn J, Shen B. Efficacy of vedolizumab in patients with antibiotic and anti-tumor necrosis alpha refractory pouchitis. Inflamm Bowel Dis 2017;23:E5–E6. 8. Bar F, Kuhbacher T, Dietrich NA et al . Vedolizumab in the treatment of chronic, antibiotic-dependent or refractory pouchitis. Aliment Pharmacol Ther 2018;47:581–587 9. Singh A, Khan F, Lopez R, et al. Vedolizumab for chronic antibiotic refractory pouchitis. Gastroenterology 2018;154:S-411, Sa1829. 10. Verstockt B, Claeys C, Van Assche G, et al . Vedolizumab can induce clinical remission in patients with chronic antibiotic-refractory pouchitis: a retrospective single-centre experience. J Crohns Colitis 2018;12 (Suppl 1):S425.